2016
DOI: 10.7314/apjcp.2015.16.18.8541
|View full text |Cite
|
Sign up to set email alerts
|

Low Coverage and Disparities of Breast and Cervical Cancer Screening in Thai Women: Analysis of National Representative Household Surveys

Abstract: Background: The coverage of breast and cervical cancer screening has only slightly increased in the past decade in Thailand, and these cancers remain leading causes of death among women. This study identified socioeconomic and contextual factors contributing to the variation in screening uptake and coverage. Materials and Methods: Secondary data from two nationally representative household surveys, the Health and Welfare Survey (HWS) 2007 and the Reproductive Health Survey (RHS) 2009 conducted by the National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 17 publications
(20 reference statements)
3
67
1
Order By: Relevance
“…examination led to increased rate of mammography. It seems that, after the diagnosis of a problem in the clinical breast exam, women are recommend to do mammography (Tolma et al, 2011;Mukem et al, 2014). There are other factors that predict indirect relationship between risk perception and repetition of mammography.…”
Section: Discussionmentioning
confidence: 99%
“…examination led to increased rate of mammography. It seems that, after the diagnosis of a problem in the clinical breast exam, women are recommend to do mammography (Tolma et al, 2011;Mukem et al, 2014). There are other factors that predict indirect relationship between risk perception and repetition of mammography.…”
Section: Discussionmentioning
confidence: 99%
“…The essential package funded in each country will depend on what is affordable. Governments may decide to offer subsidized care to a targeted population, or they may initially cover fewer interventions and increase them over time, as resource envelopes rise, as has been done in several LMICs, including Mexico 62 and Thailand 63,64 …”
Section: Situational Analysismentioning
confidence: 99%
“…HPV vaccination was introduced in 2017, as a school-based National Immunization Program only for 5th grade girls, aged 11-12 years. Two national surveys reported that the coverage rates for cervical cancer screening were 46.3% and 59.7% in 2007 and 2009, respectively [37].…”
Section: Koreamentioning
confidence: 99%